Radiatively trapped e^{±} pair plasma as a laser-to-γ photon converter - Daniel Younis; Daniel F. Gordon; Bahman Hafizi (Physical Review Research)
An energy equilibrium arises when an electron-positron pair plasma is generated by the nonlinear Breit-Wheeler interaction of a γ-ray bunch with laser photons and becomes radiatively confined. Ordinarily, ponderomotive scattering prevents leptons from accessing the high-field regions where quantum electrodynamic (QED) effects dominate, but if quantum (stochastic) radiation reaction is sufficiently strong, a balance of acceleration and recoil forces emerges. This unique scenario enables leptons to continuously mediate the transformation of laser photons into directed γ-rays via inverse Compton scattering as they copropagate with the field. Importantly, it is observed that the lepton energy stabilizes while the γ energy increases in direct proportion to laser energy depletion. The proposed scheme enables fundamental tests of QED, and is investigated here using the particle-in-cell method in full dimensionality, in addition to test-particle calculations. The per-species energy conversion efficiency is analyzed as a function of the initial laser and γ-beam properties.